Diana's Hunt (Caccia di Diana) : Boccaccio's First Fiction - Cassell, Anthony K.; Kirkham, Victoria (The Middle Ages Series, 1991)
A dual-language edition of the first major allegorical poem written by Giovanni Boccaccio. It features a revised Italian textual edition that draws on the six extant manuscripts of the original work.